Ticagrelor versus Adjusted‐Dose Prasugrel in Acute Coronary Syndrome with Percutaneous Coronary Intervention - Tsai, Ming‐Lung; Lin, Yuan; Chen, Dong‐Yi; Lin, Ming‐Shyan; Wang, Chao‐Yung; Hsieh, I‐Chang; Yang, Ning‐I; Hung, Ming‐Jui; Chen, Tien‐Hsing (Clinical pharmacology and therapeutics, 2024)
Dual antiplatelet therapy (DAPT) with ticagrelor or adjusted‐dose prasugrel has been used for acute coronary syndrome (ACS). However, few studies have directly compared these two drugs. In this study, we compared the real‐world applications and outcomes of these two drugs in patients with ACS who had undergone percutaneous coronary intervention (PCI). This retrospective cohort study was conducted using the data of eligible patients with ACS who had undergone PCI at Chang Gung Memorial Hospital System between June 2019 and December 2021. The primary efficacy‐related outcome was the occurrence of major adverse cardiovascular events (MACEs), and the primary safety‐related outcome was major bleeding. Inverse probability of treatment weighting based on propensity score was performed to reduce confounding effects. The study included 2,636 patients; of them, 429 received prasugrel and 2,207 received ticagrelor. No significant between‐group difference was observed in the risk of MACE (13.1 vs. 13.1 events per 100 person‐years, respectively, hazard ratio (HR): 1.01, 95% confidence interval (CI): 0.71–1.43). Both groups exhibited similar rates of major bleeding (3.9 vs. 4.1 events per 100 person‐years, respectively, subdistribution HR: 0.96, 95% CI: 0.68–1.35). In real‐world settings, adjusted‐dose prasugrel and ticagrelor exhibit comparable safety and efficacy profiles in East Asian patients with ACS after PCI. Our findings offer valuable insights for future clinical decision making and patient management strategies.